Implementasi Metode Mac Spoofing Pada Wifi Jammer NodeMCU ESP8266 Di Client Windows 10 - Adjie, Galah Seno; Kustanto, Kustanto; Widada, Bebas (Politeknik Indonusa Surakarta, 2022)
With the development of the increasingly fast especially in the areas of network technology, users are expected to to keep track of it so as not to lose by other users. The need for a new wifi network is becoming a basic requirement for the community both for the students and for the workers, the presence of unexpected events the client disconnected from wifi router which resulted in the absence of a direct internet connection without any warning or commonly called wifi jammer. In the current research aims to create a program for clients to avoid wifi jammer, this program works by changing the client mac address or usually called mac spoofing method which are run by the client, with a new registry file filled into the directory automatic batch file with regedit to get the new mac address. The program uses the Java netbeans GUI to simplify operations by clients, a different configs can be used automatically. The results of this program in the form of a new mac address will be shown in the program can to avoid a wifi jammer.